(untitled) (Tempo e Argumento, 2023)
Based on the concept of coloniality (the invisible and constitutive part of modernity), as discussed since the late 1980s to the early 1990s, by Aníbal Quijano, this text aims to discuss how the coloniality of power, of knowledge, of being and of nature happened in the constitution process of Manoel Enrique da Silva Forest Park, currently denominated as Irati National Forest. As sources, we have the reports produced by his forester, Ernesto da Silva Araújo, between 1950 and 1960, and 12 printed forms (FINPI) to fill in information about the plots planted in the Park between 1950 and 1957 with Araucaria angustifolia (Brazilian Pine Tree or Paraná Pine Tree). In the text, we show how scientific silviculture intended, not always successfully, to arrange a space considered by the forester as primitive. In the Araucaria plantation processes, nature was reduced to the value of land, and its diversity was limited to only one species, with monoculture being the fundamental basis of this model.